Análise da expressão dos genes Baby Boom (BBM) e Somatic Embryogenesis Receptor-like Kinase (SERK) envolvidos na embriogênese somática do cafeeiro (Coffea arabica L.) - Silva, Anderson Tadeu (2011)
This study reports the genes identified and characterized in the somatic embryogenesis of Coffea arabica L. cv Catiguá conducted at the Laboratório Central de Biologia Molecular (LCBM), at the Federal University of Lavras (UFLA), Minas Gerais. Somatic embryogenesis - the formation of the embryo starting from somatic cells, is a natural asexual reproduction mechanism in some plant species, but it can be induced in vitro in a general manner. Histological analyses of the differentiating characteristics between somatic and embryogenic cells can be used to increase methodological efficiency, however, they do not allow the diagnosis of the transition inductor events among those characteristics and, therefore, the study and obtaining of molecular markers related to the transition events are of extreme usefulness. In that context, we evaluated the in silico and in vitro expression of the SERK (Somatic Embryogensesis Receptor Kinase) and BBM (Baby Boom) genes involved in the process of transition from the vegetative state to the embryogenic, seeking the differential expression "in vitro" and also the search for a molecular marker, by in silico analyses. Article 1 presents the differential expression of the SERK gene in the embryogenic calli, non-embryogenic calli and cellular suspension stages. A total of three EST-contigs were analyzed, in which EST-contig 166 presented, in its expression, characteristics differentiated for coffee embryogenesis. That data suggest that EST-contig 166 is a possible ortholog of SERK in C. arabica (CaSERK) and indicates that that strategy can also further increase the methodological efficiency for the obtaining of embryogenic cell suspensions - ECS, in other species and cultivars. Article 2 presents the differential expression of the BBM gene in the embryogenic calli, non-embryogenic calli and cellular suspension stages. A total of two EST-contigs were analyzed, in which EST- contig 9 presented high and exclusive expression in the embryogenic calli and cellular suspension stages, in relation to the non-embryogenic calli. That data suggest that EST-contig 9 is a possible BBM ortholog in C. arabica (CaBBM) and indicates that its use as a molecular marker can further increase the methodological efficiency during the obtaining of coffee plant embryogenic materials. Article 3 indicates a transient induction relationship and retroinhibition between CaBBM and CaSERK during the ECS growth curve, in the which the diametrically opposed expression between them coincides with the stabilization of the ECS growth rate. Article 4 presents the possibility that five EST-contigs, identified in silico in the coffee libraries, can also be used as embryogenesis acquisition process markers.